Ընտանիքում կոնֆլիկտների առաջացման պատճառները և հաղթահարման ուղիները փոխակերպվող հասարակության մեջ - Ասատրյան, Գայանե (Զանգակ հրատ.)
В статье исследуются ключевые изменения, происходящие в современном обществе,которые влияют на жизнедеятельность семейной структуры, на изменения дифференциации возрастно-гендерных ролей. Нами проанализированы проблемы кризиса института семьи в Армении, изучены типы семейных конфликтов, а также внутренние и внешние факторы их возникновения. Представлены варианты решения семейных конфликтови пути их преодоления. Fundamental transformations of the modern society are presented in the article, which lead to the separation and changes of the family life, structure, gender and age based roles. The issues of the family institution crisis in Armenia are analyzed, and it is investigated the impact of the transforming society changes into the family, the types of family conflicts and the internal and external factors of the conflicts occurrence. Also family conflicts accomplishment options, the opportunities and ways to overcome them are presented.
Keywords: Հոգեբանություն